Changes in retail industry in the EU - Knezevic, Blazenka; Renko, Sanda; Knego, Nikola (Business, Management and Economics Engineering, 2011)
Retail is an important industry of each national economy. In the EU, it is an important source of employment and significantly contributes to the GDP creation. Moreover, almost one fifth of all companies are registered in retail industry. In the past decade, retail industry is changing from applying domestically oriented towards internationally oriented business strategies. The importance of large companies is this industry is growing, too. Retail trade concentration process is recognized in all EU countries. In this paper, some of prevailing trends in retail industry are analyzed and explained. The analysis includes EU countries and Croatia as EU candidate country.